2019
DOI: 10.1002/hpja.261
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the pathways between recreational cannabis use and mood disorders: A Behaviour Sequence Analysis approach

Abstract: Issues Addressed Although cannabis use is still illegal in most places around the world, it remains a widely used drug. The recreational use of cannabis has been linked to multiple mental wellbeing issues, including psychosis, depression and anxiety. The objective of this study was to investigate the temporal dynamics of cannabis use in relation to mental health issues. Methods The current research uses a novel methodological approach, behaviour sequence analysis, to understand the temporal relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…While observational studies have suggested that heavy cannabis use may unveil depressive or psychotic episodes 12 , there are many biopsychosocial factors involved. 33 , 34 This discussion is further complicated by recent trends of cannabis and synthetic cannabinoids being used as self-medication or prescribed as experimental therapy for acute and chronic psychiatric disorders. While there is literature in support of its therapeutic value and safety for chronic pain, 35 , 36 multiple sclerosis, 37 cancer, 38 and inflammatory bowel disease, 39 the evidence for prescribing cannabis for the symptomatic treatment of psychotic, anxiety, or mood disorders is scarce and mixed.…”
Section: Discussionmentioning
confidence: 99%
“…While observational studies have suggested that heavy cannabis use may unveil depressive or psychotic episodes 12 , there are many biopsychosocial factors involved. 33 , 34 This discussion is further complicated by recent trends of cannabis and synthetic cannabinoids being used as self-medication or prescribed as experimental therapy for acute and chronic psychiatric disorders. While there is literature in support of its therapeutic value and safety for chronic pain, 35 , 36 multiple sclerosis, 37 cancer, 38 and inflammatory bowel disease, 39 the evidence for prescribing cannabis for the symptomatic treatment of psychotic, anxiety, or mood disorders is scarce and mixed.…”
Section: Discussionmentioning
confidence: 99%
“…A growing wealth of research shows the cognitive, social, and developmental predictors of violence, future research could stratify the sample into individuals with different demographics or measurement scores. Taking a typology approach to BSA would be more akin to recent research (e.g., Keatley et al, 2019), in which different typologies of serial killers showed different sequences, or Marono et al (2018) research into different personality clusters and deception. Therefore, measuring individual’s personality and developmental backgrounds might offer clearer sequential predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on violent outbursts as isolated events provides a basic approach to understanding precursors of violent episodes; however, a more useful approach when attempting to understand real-world, dynamic behaviors is Behavior Sequence Analysis (BSA; Clarke & Crossland, 1985; Keatley, 2018). BSA has been used in a number of applied settings, especially in the area of Forensic Psychology and Criminology (Keatley et al, 2019; Taylor et al, 2008). BSA is underpinned by statistical analysis of the interdependence between individual behaviors and events.…”
Section: Introductionmentioning
confidence: 99%
“…This is the basic approach of behavior sequence analysis (BSA; Keatley, 2018), which has been applied to real-world cases of homicides (Keatley, Golightly, Shephard, Yaksic, & Reid, 2018), violence (Taylor et al, 2017), stalking (Quinn-Evans, Keatley, Arntfield, & Sheridan, 2019), drugs (Keatley, Walters, Parke, Joyce, & Clarke, 2019), and sexual assault and rape cases (Ellis, Clarke, & Keatley, 2017; Fossi, Clarke, & Lawrence, 2005; Lawrence, Fossi, & Clarke, 2010). In each application, the premise remains the same: what behaviors are observed and in what order do they occur.…”
Section: Systems Approachmentioning
confidence: 99%